Growth Performance of Male Line of Superior Tropical Rabbit - B. Brahmantiyo; N. Pratiwi; F. Saputra; Y. C. Raharjo; L. H. Prasetyo (Faculty of Animal Science, Bogor Agricultural University, 2021)
New Zealand White rabbits (NN) are known as broiler rabbits that are well adapted to the Indonesian environment. HyLa rabbits are rabbits imported from China that were selected for high reproduction and growth rates. The increased productivity of NN rabbits was achieved by crossing to HyLa rabbits. This study was aimed to evaluate HyLa and NN rabbits’ productivity and their reciprocal crosses to develop a broiler rabbit adaptive to tropical climate. Forty heads of does and 20 heads of bucks of HyLa rabbit, 30 heads of does, and 6 heads of bucks of New Zealand White rabbits (NN) were used. Reproductive performance of does (litter size at birth, litter size at weaning, mortality, and weekly does body weight) and the kit’s growth performance (weekly body weight from weaning until the age of 20 weeks) was evaluated. Data were analyzed using the SAS program, FactoMineR, and factoextra package in R 4.0.0. Rabbit’s growth data were periodically analyzed by the Gompertz model. At the age of 10 weeks, HyLa had a body weight of 1459.7 ± 373.1 g greater than HyLa x NN (1380.1 ± 389.9 g), NN x HyLa (1225.7 ± 263.4 g), and NN (985.0 ± 234.4 g). Based on the Gompertz model, NN x HyLa had an inflection point at a weight of 1,977.7 at 12 weeks. Furthermore, NN x HyLa had a better litter size than HyLa x NN. NN bucks x HyLa does have the potential to be developed as a superior rabbit adaptive to tropical climate.